Pengembangan Bahan Ajar Bahasa Arab Berbasis Pendekatan Komunikatif - Aflisia, Noza; Hazuar, Hazuar (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This study aims to develop Arabic teaching materials with a communicative approach for MA Muhammadiyah Curup students by analyzing the needs and validation / feasibility of Arabic teaching materials with the communicative approach according to experts' assessments. Researchers develop teaching materials based on this communicative approach aimed at improving students' ability in mastering Arabic which is not only theoretical but also practical and communicative. Data collection techniques using observation, questionnaires, interviews, and documentation. Likert scale is used for questionnaires and qualitative data analysis techniques using data reduction, data display, and verification. The results showed that Arabic teaching materials that have been used are not yet relevant to the needs of students and have not maximally improved students' Arabic speaking skills. The development of Arabic language teaching materials compiled is based on the results of planning and design development with three themes namely Al-Bayanaats Ash-Syakhshiyyah, Al-Hayah fil Usrah, and Al-Murafiq Al-mmAmmah fil Madrasah. This Arabic module has 28 pages. The average value of the validator for the initial design of this Arabic teaching material module is 22.87 with a very good category.